Verbatim Record of the Nineteenth Meeting (Closed) - Héderváry, Claire de (1957)
Records of this digital collection were assembled to document the work of the UN Special Committee on the Problem of Hungary established on January 10, 1957 by the United Nations General Assembly for the purpose of investigating the 1956 Hungarian revolution. Principal contributor(s): United Nations Special Committee on the Problem of Hungary János Horváth, economist, a member of the Independent Smallholders' Party, and elected member of the Parliament 1945-1947. In his statement, Horváth spoke about the communist government before the revolution, then about the events he witnessed as a freedom fighter. The committee asked questions in connection with his statement, details of the negotiations he participated in with the government, and the situation of the churches. Witness D, who worked in the Central Statistical Office in Budapest, made his statement and answered questions from the committee relating to his statement.